Phytoclimatic versatility and potential diversity of natural arboreal forest cover in peninsular Spain - Garcia Lopez, J M; ALLUÉ CAMACHO, C (INVESTIGACION AGRARIA-SISTEMAS Y RECURSOS FORESTALES, 2008)
A multivariate methodology was assayed to evaluate the phytoclimatic versatility of peninsular Spain and how this relates to the potential diversity of natural tree covers. The instances of greatest phytoclimatic versatility occur in a range of altitude between 1000 and 1300 m; these are cool phytoclimates with only short, low-intensity periods of aridity. These factorial ambits of maximum versatility correspond chiefly to the substeppe nemoral subtype VI(VII), followed by genuine nemoral VI and humid nemoromediterranean VI(IV)(2) subtypes. The lowest values of versatility and potential diversity correspond to dry genuine Mediterranean (IV(1)) or transitional Mediterranean IV(VI)(1) subtypes and to alpine oroborealoid or oroarcticoid subtypes. In geographical terms, intermediate mountain areas in the north of the Peninsula and some massifs in the southern half score the highest in the Diversity Index used. The lowest scores are found in the southern half of the Peninsula, although in the northern half low scores are also found for littoral areas, interior areas of the Duero and Ebro basins and alpine areas. Autoecological phytoclimatic spectra headed by stands of Pinus nigra and Quercus petraea present the greatest phytoclimatic versatility, while those headed by Quercus ilex ballota and Pinus uncinata stands present the least versatility. This article offers new methodological horizons for the study of the effects of climate change on plant diversity.
Keywords: Biodiversity; climate change; competition; Simpson Index; suitability